Ambroise Paré (1510 to 1590): A Surgeon Centuries Ahead of His Time. Issue 6 (June 2014) - Shen, James T.; Weinstein, Michael; Beekley, Alec; Yeo, Charles; Cowan, Scott
In their extensive writings, Hippocrates and Celsus counseled physicians to be knowledgeable in both the medical and surgical management of patient recovery. 1 However, their words fell by the wayside because cutting of the body was forbidden by the Roman Catholic Church. Furthermore, the contemporaneous Arabic medical teachings emphasized tradition and authority over observation and personal experience. This created an ever-growing rift between the schools of surgical and pharmacologic medicine with both groups denying their involvement in the other domain. Surgeons had been plagued by postoperative complications including infection, malnutrition, and muscular wasting for centuries. Surgeons were forced to re-examine how diet and exercise affected outcomes before the advent of microbiology and advances in pharmacology. All of this changed when Ambroise Paré, a 16th century surgeon, revolutionized the medical world with his astute observations of postoperative diet and exercise.